Adenoid Cystic Carcinoma of the Nasopharynx : A Case Series - Ng, Boon Han Kevin; Tang, Ing Ping (Springer India, 2019)
Adenoid cystic carcinomas are tumors that are more commonly seen in the salivary glands than in the nasopharynx. Nasopharyngeal adenoid cystic carcinomas are rare and cases that are reported in the literatures are few. Treatment is mainly by surgical resection. Here, we report 2 cases of nasopharyngeal adenoid cystic carcinoma.